Volcano flank instabilities and lateral collapse - Capra Lucia; Belousov Alexander; Bernard Benjamin; Dufresne Anja; Le Friant Anne; Paguican Engielle Mae R.; Roverato Matteo; van Wyk de Vries Benjamin; Watt Sebastian F.L. (My University, 2025)
The gravitational instability and subsequent lateral collapse of a volcano is a common phenomenon observed in most types of volcanoes, from continental to oceanic environments. Both intrinsic and extrinsic factors contribute to volcanic collapse, including the volcano's internal structure, geological setting, and a range of volcanic and non-volcanic processes, including climatic conditions. Lateral collapse typically leaves a scar on the volcano's flank and produces a corresponding debris avalanche deposit. Debris avalanched deposits are characterized by distinct morphological features and internal facies that can reveal the causes of the instability and the interaction of the failure mass with the surrounding substrate and landscape. Lateral collapses can trigger secondary hazards such as magmatic and phreatic eruptions, tsunamis, lahars, river obstructions with the formation of natural dams, and submarine landslides, leading to potentially catastrophic environmental effects. Studying volcanic landslides is fundamental for improving our scientific knowledge of this geological process and understanding their associated hazards in the short and long term. Such knowledge can enhance social awareness, promoting urban resilience and ecosystem protection.
Keywords: Volcanic lateral collapse; flank instability; volcanic landslides; volcanic debris avalanche; volcano spreading; debris avalanche facies; hummock; jigsaw crack